Editorial. (February 2016) - Mansfield-Devine, Steve
Abstract : Online advertising is turning into something of an arms race. On one side – the Evil Empire, if you like – there's the advertising industry trying to persuade us to buy stuff we didn't realise we wanted (and probably don't). On the other side are people who dislike advertising and don't want their browsers cluttered with it. And just as with a real arms race, there are casualties, one of which is security.